Penyalahgunaan Wewenang Direksi Perseroan Terbatas Atas Pengalihan Aset Perusahaan - Icha Rahmawati; Hotimah Hotimah; Sumriyah Sumriyah (Jurnal Hukum dan Sosial Politik, 2023)
The organ of the company in carrying out its management functions is the Board of Directors. The Board of Directors is one of the company's organs. In the company, directors have obligations that must be carried out. The negligence committed by the board of directors has the right to be held accountable and can be subject to sanctions. These actions can be detrimental to the company, and can lead to legal consequences of the actions that have been committed. It is better for the directors to ask for approval in advance in the company's GMS, but this is not done by the directors and only takes their own policies aimed at taking their own benefits which can clearly be detrimental to the company, because these assets belong to the company. From this background, in this issue what is discussed is how to analyze the abuse of authority of limited company directors over the use of company assets. This type of research belongs to normative law where the work done is to process data related to the problem, besides that this research can also be seen from its nature, literature research, library research, using legal literature materials related to the problem under study.